Kinetic Alfven waves excited by multiple free energy sources in the magnetotail - Barik, K. C.; Singh, S. V.; Lakhina, G. S. (My University, 2023)
The generation of kinetic Alfvén waves (KAWs) is investigated through a three-component theoretical model incorporating ion beam and velocity shear as the sources of free energy in a non-Maxwellian κ-distributed plasmas. The model considers Maxwellian distributed background ions, drifting-Maxwellian beam ions, and κ-electrons as its constituent species. It is found that the combination of either positive velocity shear with counter-streaming beam ions or parallel streaming beam ions with negative velocity shear favors the excitation of KAWs. The effect of the κ-parameter on the excitation of KAWs under the combined energy sources is explored. The effect of plasma parameters such as number density, propagation angle, and temperature of plasma species on the real frequency and the growth rate of KAWs are examined. For the plasma parameters pertinent to the magnetotail region of Earth’s magnetosphere, the model is able to produce KAWs in the frequency range of ≈(5–67) mHz, which matches well with the recent ‘Time History of Events and Macroscale Interactions during Substorms (THEMIS)’ observations in the near-Earth magnetotail region.
Keywords: Solar wind; Alfven waves; Space plasmas